Board Diversity and Firm Performance: Malaysia Context - Mohd Waliuddin, Mohd Razali; Nursyuhada, Abdul Aziz; Janifer, Lunyai (Unimas Publisher, 2018)
The large firms like Enron, WorldCom and Freddie Mac were involved in the crisis and the bankruptcy of corporate frauds and accounting scandals which were lack of effectiveness of their board of directors in those firms. Great board diversity will affect the firm performances in term of return on asset (ROA) and return of equity (ROE). This research used data of 385 samples of annual reports listed companies in Bursa Malaysia for the period of 2014 to 2016 were obtained and examined. The independent variables of board diversities are women in the board, board size, boards‟ educational level and the boards‟ experiences and control variables; firm size and firm leverage. After controlling the variables, the research shows only female has negatively significant towards ROE. It is because the number of female in board is very small. It also can be concluded that women have no power in board which the needed of them in making decision is low. For the control variables, firm size has positively significant towards ROA and ROE. Then, the firm financial leverage has a negatively significant towards ROA and ROE. For the future research, researchers are recommended for use other variables for board diversity such as board age and board independent and also use a long period of research such as for 5 to 10 years.